The order study of the sentence elements in Ferdowsi’s Shahnameh: (the story of Rostam, Sohrab and Siavash) - Safar, Hasan Ali (Al-Adab Journal, 2019)
The examination and grammatical study of the texts of classical prose and order, is very important in recognizing these works. So far, various scholars have examined the classical text with a grammatical view. In this article, the author examined the story of Siavash, Rostam and Sohrab, by focusing on the order of elements and components of the sentence. The results of the research show that the frequency of sentences with disorder in the disorganization of the word, is high in Shahnameh. The most important rhetorical and linguistic features of Shahnameh can be found in word-formation, linguistic patterns, vocabulary combinations and verb attributes. In this part of the article, we extracted a group of sentences. First, we achieved a general category. In this category, we divided the sentences into two sections; ordered sentences and uneasy sentences. In ordered sentences, the elements and components of the word are arranged in the usual and conventional order, and in uneasy sentences, the sentences which are disordered are listed. In addition, the ordered sentences are sorted into two categories; ordered type 1 and ordered type 2. In the ordered sentences type 1, the sentences are made based on the pattern “subject + verb conjugation + verb”, and the word pattern in ordered sentences type 2, is “verb conjugation + subject + verb”. One of the most important features of these sentences is the verb precedence in the sentence. This application is done with different purposes. One of the most important purposes is the observation of the rules of word rhythm and tone. The next option, which is another reason for the approach, is the emphasis on actions. Increasing the precedence in verb and the high frequency of this type of sentences’ application in Shahnameh, indicates the importance and emphasis of actions in Shahnameh. Since Shahnameh is a pragmatic text, action and verb play an important role in it. Also, the presence of the verb at the beginning of the sentence, is the emphasize on the importance of the verb and the action of the persons in the story. The results showed that the ordered sentences type 1, 35 cases, ordered sentences type 2, 18 cases, and uneasy sentences has 62 cases abundance. These statistics show that the frequency of uneasy sentences or in the other words, sentences without respect for the order of word components, is high. This application, in addition to observing the rhythm and tune of the word, goes back to the purpose and mission of the word and the epic tune. The importance of actions and emphasis on verbs, is another achievement of Shahnameh to this type of applications.